2013
DOI: 10.1016/j.bbadis.2013.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin knockout accentuates high fat diet-induced obesity and cardiac dysfunction: Role of autophagy

Abstract: Adiponectin (APN), an adipose-derived adipokine, offers cardioprotective effects although the precise mechanism of action remains unclear. This study was designed to examine the role of APN in high fat diet-induced obesity and cardiac pathology. Adult C57BL/6 wild-type and APN knockout mice were fed a low or high fat diet for 22 weeks. After 40 day feeding, mice were treated with 2 mg/kg rapamycin or vehicle every other day for 42 days on respective fat diet. Cardiomyocyte contractile and Ca2+ transient proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
102
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(115 citation statements)
references
References 63 publications
11
102
1
1
Order By: Relevance
“…Other studies have shown increased weight gain in response to HF diet for 22 weeks, 23 we think that the difference in results can be attributed to the shorter 12-week duration of our study. This duration of 12 weeks of high fat diet decreased adiponectin mRNA in adipose tissue of WT mice.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Other studies have shown increased weight gain in response to HF diet for 22 weeks, 23 we think that the difference in results can be attributed to the shorter 12-week duration of our study. This duration of 12 weeks of high fat diet decreased adiponectin mRNA in adipose tissue of WT mice.…”
Section: Discussioncontrasting
confidence: 46%
“…This duration of 12 weeks of high fat diet decreased adiponectin mRNA in adipose tissue of WT mice. The animals used in the earlier study were 4 mo of age 23 ; we have compared 11-mo-old WT and ADKO mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the presence of an additional stress such as ischemia and reperfusion (I/R), high fat-fed hearts become more prone to cardiac injury due to impaired autophagy ( 15 ). In the long-term, HFD mice eventually develop contractile dysfunction in parallel with impaired autophagy ( 41 ). These data suggest that impairment in autophagic turnover may heighten sensitivity to stress and may progressively contribute to contractile dysfunction in diet-induced obesity.…”
Section: Pkc ␤ Regulates Nox2-activity In Palmitate-treated Cmsmentioning
confidence: 80%
“…As cardiac hypertrophy is an important feature of diabetic cardiomyopathy (DCM) (Nunes et al 2013), we speculate that perigestational exposure to HFA may program female progeny to develop DCM, increasing the risk of heart failure (Boudina & Abel 2010, Nunes et al 2013. Strikingly, hyperglycemia (Murarka & Movahed 2010), hyperinsulinemia (Boudina & Abel 2010, Murarka & Movahed 2010, and adiponectin deficiency (Guo et al 2013), all manifested in HFA female offspring, have been suggested to contribute to cardiac hypertrophy (Guo et al 2013).…”
Section: Discussionmentioning
confidence: 99%